2014
DOI: 10.1111/tct.12109
|View full text |Cite
|
Sign up to set email alerts
|

What do medical students expect in a teacher?

Abstract: Medical students' preference for one teacher over another is directly correlated with a teacher's ability to teach, his or her interpersonal skills, as well as personal and professional qualities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 9 publications
(6 reference statements)
1
7
0
2
Order By: Relevance
“…In his study students preferred communication and personal skills compared with teaching, as in the present study. 11 Teaching skills followed by inter-personal skills were ranked as important skills in a study by Kiani et al, 16 these results were somewhat similar to this study because in our study faculty's personal attributes were given more importance.…”
Section: Discussionsupporting
confidence: 89%
“…In his study students preferred communication and personal skills compared with teaching, as in the present study. 11 Teaching skills followed by inter-personal skills were ranked as important skills in a study by Kiani et al, 16 these results were somewhat similar to this study because in our study faculty's personal attributes were given more importance.…”
Section: Discussionsupporting
confidence: 89%
“…Further, written comments suggested that interaction and discussion may have been influenced by participating consultants and registrars. Indeed, a teacher's ability to teach, his/her interpersonal skills, and his/her personal/professional abilities may influence learners' preference for that teacher [55]. Moreover, the subject-specific enthusiasm teachers convey may directly relate to learners' performance [56].…”
Section: Discussionmentioning
confidence: 99%
“…Muitas dessas atitudes também foram apontadas como importantes em outros estudos 1 . Em um estudo que avaliou a percepção de estudantes de Medicina sobre as qualidades essenciais de um professor, as características pessoais capacidade de liderança, organização nas atividades, inteligência, capacidade de se expressar e estímulo do raciocínio ético foram bastante valorizadas 6 . A mudança de paradigma do professor tradicional, transmissor do conhecimento, para aquele que, sendo um modelo para os seus estudantes, assume o papel de facilitador da aquisição de conhecimentos transforma essa capacidade numa peça fundamental no processo de aprendizagem 7 .…”
Section: Gráficounclassified